Defective CFTR leads to aberrant β-catenin activation and kidney fibrosis - Jie Ting Zhang (Nature Portfolio, 2017)
Abstract Cystic fibrosis transmembrane conductance regulator (CFTR), known as a cAMP-activated Cl− channel, is widely expressed at the apical membrane of epithelial cells in a wide variety of tissues. Of note, despite the abundant expression of CFTR in mammalian kidney, the role of CFTR in kidney disease development is unclear. Here, we report that CFTR expression is downregulated in the UUO (unilateral ureteral obstruction)-induced kidney fibrosis mouse model and human fibrotic kidneys. Dysfunction or downregulation of CFTR in renal epithelial cells leads to alteration of genes involved in Epithelial-Mesenchymal Transition (EMT) and kidney fibrosis. In addition, dysregulation of CFTR activates canonical Wnt/β-catenin signaling pathways, whereas the β-catenin inhibitor reverses the effects of CFTR downregulation on EMT marker. More interestingly, CFTR interacts with Dishevelled 2 (Dvl2), a key component of Wnt signaling, thereby suppressing the activation of β-catenin. Compared to wild type, deltaF508 mice with UUO treatment exhibit significantly higher β-catenin activity with aggregated kidney fibrogenesis, which is reduced by forced overexpression of CFTR. Taken together, our study reveals a novel mechanism by which CFTR regulates Wnt/β-catenin signaling pertinent to progression of kidney fibrosis and indicates a potential treatment target.